Wiara i niewiara w Boga amerykańskich uczonych - Drozdowicz, Zbigniew (Polskie Towarzystwo Religioznawcze, 2019)
In common views scholars belong to a group of people either non-believing in the existence of God and his creational powers, or at least distancing themselves from several of such beliefs which is shared by the majority of the society. The research in this matter shows that this issue is quite diverse when put into practice, also in such a leading in scientific achievements country like the United States. Although this research confirms that the major part of American scholars is either people declaring their non-faith in God, or at least distancing themselves in a significant way from it, there are many (both in social and natural sciences) of them who accept beliefs which seem to be in a striking contradiction with the knowledge on man and the natural world. One of such people recalled in these remarks is Alvin C. Planting. His argument with Daniel Dennett shows how far the standards of scientific correctness of thought accepted by American scholars might differ.
Keywords: new theism; new atheism; boundaries of faith and non-faith of American scholars